Contribution of the Microbiome, Environment, and Genetics to Mucosal Type 2 Immunity and Anaphylaxis in a Murine Food Allergy Model - Stark, Kelsey G.; Falkowski, Nicole R.; Brown, Christopher A.; McDonald, Roderick A.; Huffnagle, Gary B. (Frontiers in Allergy, 2022)
There is heterogeneity inherent in the immune responses of individual mice in murine models of food allergy, including anaphylaxis, similar to the clinical heterogeneity observed in humans with food allergies to a defined food. One major driver of this heterogeneity may be differences in the microbiome between sensitized individuals. Our laboratory and others have reported that disruption of the microbiome (dysbiosis) by broad spectrum antibiotics and/or yeast colonization can alter systemic immunity and favor the development of mucosal Type 2 immunity to aeroallergens. Our objective was to use a well-characterized murine model (Balb/c mice) of food allergies (chicken egg ovalbumin, OVA) and determine if antibiotic-mediated dysbiosis (including C. albicans colonization) could enhance the manifestation of food allergies. Furthermore, we sought to identify elements of the microbiome and host response that were associated with this heterogeneity in the anaphylactic reaction between individual food allergen-sensitized mice. In our dataset, the intensity of the anaphylactic reactions was most strongly associated with a disrupted microbiome that included colonization by C. albicans, loss of a specific Lachnoclostridium species (tentatively, Lachnoclostridium YL32), development of a highly polarized Type 2 response in the intestinal mucosa and underlying tissue, and activation of mucosal mast cells. Serum levels of allergen-specific IgE were not predictive of the response and a complete absence of a microbiome did not fully recapitulate the response. Conventionalization of germ-free mice resulted in Akkermansia muciniphila outgrowth and a higher degree of heterogeneity in the allergic response. C57BL/6 mice remained resistant even under the same dysbiosis-inducing antibiotic regimens, while changes in the microbiome markedly altered the reactivity of Balb/c mice to OVA, as noted above. Strikingly, we also observed that genetically identical mice from different rooms in our vivarium develop different levels of a Type 2 response, as well as anaphylactic reactions. The intestinal microbiome in these mice also differed between rooms. Thus, our data recapitulate the heterogeneity in anaphylactic reactions, ranging from severe to none, seen in patients that have circulating levels of food allergen-reactive IgE and support the concept that alterations in the microbiome can be one factor underlying this heterogeneity.